Novel MYO1D Missense Variant Identified Through Whole Exome Sequencing and Computational Biology Analysis Expands the Spectrum of Causal Genes of Laterality Defects - Alsafwani, Rabab Said; Nasser, Khalidah K.; Shinawi, Thoraia; Banaganapalli, Babajan; ElSokary, Hanan Abdelhalim; Zaher, Zhaher F.; Shaik, Noor Ahmad; Abdelmohsen, Gaser; Al-Aama, Jumana Yousuf; Shapiro, Adam J.; O. Al-Radi, Osman; Elango, Ramu; et al. (Frontiers in Medicine, 2021)
Laterality defects (LD) or asymmetrically positioned organs are a group of rare developmental disorders caused by environmental and/or genetic factors. However, the exact molecular pathophysiology of LD is not yet fully characterized. In this context studying Arab population present an ideal opportunity to discover the novel molecular basis of diseases owing to the high rate of consanguinity and genetic disorders. Therefore, in the present study, we studied the molecular basis of LD in Arab patients, using next generation sequencing method. We discovered an extremely rare a novel missense variant in MYO1D gene (Pro765Ser) presenting with visceral heterotaxy, left isomerism with polysplenia syndrome. Proband in this index family has inherited this homozygous variant from her heterozygous parents following the autosomal recessive pattern. This is the first report to show that MYO1D genetic variant causing Left-Right axis in humans, besides previous known evidence from Zebra fish and Drosophila models. Moreover, our multilevel bioinformatics based structural (protein variant structural modelling, divergence, and stability) analysis has suggested that Ser765 causes minor structural drifts and stability changes, potentially affecting the biophysical and functional properties of MYO1D protein like calmodulin binding and microfilament motor activities. Functional bioinformatics analysis has shown that MYO1D is ubiquitously expressed across several human tissues and is reported to induce severe phenotypes in knock-out mice models. In conclusion, our findings show the expanded genetic spectrum of LD, which could potentially pave way for the novel drug target identification, and development of personalised medicine for high-risk families.